Etnoagronomía: Una alternativa para el desarrollo rural en México - Noriero-Escalante, Lucio (Agroecología Global. Revista Electrónica de Ciencias del Agro y Mar, 2021)
The crisis of the rural sector in productive and environmental matters; they can unleash other alternative development processes to the hegemonic ones. Ethnoagronomy, as an emerging approach when resuming the synthesis of peasant knowledge present in traditional agriculture, establishes guiding principles for efficient management of the use and management of natural resources. The objective of this work is to describe the importance of ethnoagronomy, to establish sustainable production strategies within a framework of human resource training in agronomic institutions. It is based on an ethnographic study of a hermeneutical nature. It is concluded that it is necessary to incorporate curricular lines and study plans, at the middle and higher education level, that contain guiding principles that prioritize and recognize the feelings and thoughts of the subjects who are considered the depositories of the transformation. productive and social in rural areas.